A Survey of MIKC Type MADS-Box Genes in Non-seed Plants: Algae, Bryophytes, Lycophytes and Ferns - Thangavel, Gokilavani; Nayar, Saraswati (Frontiers in Plant Science, 2018)
MADS box transcription factors have been studied extensively in flowering plants but remain less studied in non-seed plants. MADS box is one such example of a gene which is prevalent across many classes of plants ranging from chlorophyta to embryophyta as well as fungi and animals. MADS box transcription factors are of two types, Type I and Type II. Type II transcription factors (TF) that consist of a MADS domain, I region, K domain, and C terminal domain are discussed in this review. The Type II/ MIKC class is widespread across charophytes and all major lineages of land plants but unknown in green and red algae. These transcription factors have been implicated in floral development in seed plants and thus the question arises, “What is their role in non-seed plants?” From the studies reviewed here it can be gathered that unlike seed plants, MIKCC genes in non-seed plants have roles in both gametophytic and sporophytic generations and contribute to the development of both vegetative and reproductive structures. On the other hand as previously observed in seed plants, MIKC* genes of non-seed plants have a conserved role during gametophyte development. With respect to evolution of MIKC genes in non-seed plants, the number of common ancestors is probably very few at each branch. The expansion of this gene family in seed plants and increased plant complexity seem to be correlated. As gradually the genomes of non-seed plants are becoming available it is worthwhile to gather the existing information about MADS box genes in non-seed plants. This review highlights various MIKC MADS box genes discovered so far in non-seed plants, their possible roles and an insight into their evolution.